Centre for Modern Languages organise EKSA Week - Muhamad Aizat, Zulkifli; Nurul Nadia, Muhammad (UMPSA, 2023)
PEKAN, 24 July 2023 - In line with the university’s efforts and commitment to a sustainable and environmentally friendly campus approach, the Centre for Modern Languages (CML), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) organised a Public Sector Conducive Ecosystem Week (EKSA) on 24 to 28 July.